Analyses of rain fade countermeasure technique time diversity at 38 GHz - M. Saad, Nor Wahida; Ismail, Ahmad Fadzil; Asnawi, Ani Liza; Tharek, A.R.; Din, Jafri (2013)
Based on Shannon’s capacity theorem, high frequencies offer high recompense. The implementation of high frequencies for satellite communication system is imperative to be thoroughly studied and explored, especially in the tropical environment where rain is copious. In this region, hydrometeors effect especially rain attenuation is the factor that bounds the implementation of high frequency on such system. Thus, this study embarks on the analyses of time diversity as rain fade countermeasure technique at 38GHz aka V-band frequency